REVIEW: Biology and Conservation of Genus Myristica in Indonesia (Biodiversitas Journal of Biological Diversity, 2016)
Genus Myristica represent one of important taxon in kingdom plantarum in Indonesia meaning if evaluated from number of species, distribution of species, and role for society. Result of publicizing indicate that there are 9 species Myristica in Indonesia representing original crop and distributed the round of main island in Indonesia. Member of genus Myristica this type of a lot of exploited upon which the food, industrial raw material, construction material, etc. Because thatâ€™s important role hence the effort conservation must be done in order to the Myristica sustainability can be taken care of.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: Myristica, biology and conservation, Indonesia.